Genesis and Predictive Ability of Ecosystem Approach in Education - Diana Koroleva; Tatiana Khavenson; Daria Tomasova (Foresight and STI Governance)
The landscape of education is progressively diversifying, characterized by an influx of various new participants, products, technologies, and institutional configurations. The concept of a comprehensive educational ecosystem is increasingly invoked. Yet, our understanding of the educational ecosystem phenomenon remains fragmented and lacking structure. This limitation poses obstacles to both engaging in a scholarly discourse and fully harnessing the predictive potential inherent in the ecosystem approach. The objective of this article is to delineate the practices involving interaction, knowledge exchange, and the diffusion of innovation among participants and strata within the educational realm. These practices serve as the foundation for the processes underpinning its development and transformation, culminating in the educational sphere acquiring ecosystemic attributes. This paper contributes to the conceptualization of an educational ecosystem founded upon the principles of an open and dynamic social system. It emphasizes the coevolution of stakeholders, a high degree of resource and competency complementarity, and collaborative competition in the creation of novel educational products. We expound upon the evolutionary origins of the educational ecosystem concept, attributing its development to the emergence of new actors and the expansion of communication capabilities for information dissemination and interactive linkages.We also underscore the continuity of the educational ecosystem concept concerning the triple, quadruple, and five helix models. Consequently, we propose a methodology for applying the ecosystem approach to conduct foresight studies and engage in co-design endeavors aimed at realizing the Sustainable Development Goals within the realm of education. This methodology aligns with the foundational principles articulated in the UN Sustainable Development Goals for Education until 2030 (Strategic Development Goal 4 - SDG4). The ecosystem approach is harnessed in the selection of source materials, the interpretation of prospective indicators, and the description of foresight subjects. In doing so, we affirm the predictive capacity of the ecosystem approach in modeling novel forms of stakeholder interactions, delineating the coevolution of social, economic, technological, and cultural trajectories, and identifying equitable and collectively significant priorities for the advancement of the educational milieu.